Effect of Accounting Information Systems, E-Commerce, Knowledge of Accounting as a Motivator for Accounting Students Against Entrepreneurial Interests - Putri, Oktavira Tiara; Linawati, Linawati; Solikah, Mar’atus (Universitas Nusantara PGRI Kediri, 2023)
Research Objective: The purpose of this study was to determine the interest in entrepreneurship of accounting students at Nusantara University PGRI Kediri in accounting information systems, e-commerce, accounting knowledge. Research Method: Quantitative research was used in this study. This study relies on primary data collected through questionnaires. Sampling was carried out using the purposive sampling method for accounting students who had taken accounting information systems courses in 2019 and 2020. Data analysis techniques and hypothesis testing were done using SPSS version 21 software. Research Finding: According to the findings of this study, the information system has a positive effect on interest entrepreneurship, e-commerce has no effect on entrepreneurial interest and accounting knowledge has a positive effect on entrepreneurial interest.